STRATEGI PENGEMBANGAN USAHA PELAKU BISNIS RITEL DALAM PERSPEKTIF EKONOMI ISLAM (Studi Kasus Masyarakat Penjual Eceran Sekitar Top Swalayan Kolaka) - Sakia Pajriani; Muh Asra; Ibrahim Tawile (Jurnal Ekonomi Bisnis Syariah, 2020)
Retail business or better known as retail business is a trading activity in which there are goods and services in which retail business actors sell their goods to the end consumer. This retail business or retail business sells various kinds of daily necessities needed by the community.The formulation of the problem in this research is how the strategies of retail business actors in developing their business and what are the supporting and inhibiting factors in developing a retail business and their solutions. The purpose of this study is to determine the strategies of retail business actors in developing their business and to determine the supporting and inhibiting factors in the development of retail businesses and their solutions.This research is a descriptive study, using a qualitative approach with the subject of the Business Development Strategy of Retail Business Players in the Perspective of Islamic Economics and what problems occur and their solutions. Then the research procedure carried out includes intensive observation (Observation, Interview and Documentation) regarding the Business Development Strategy of Retail Business Actors and what problems occur and their solutions.The results show that the development strategy of retail business actors in developing their business uses strategies that can actually make the business more developed, namely by expanding the business network in Pasar Raya Mekongga, promoting merchandise, getting new customers, writing income and spending, providing services. which is good for consumers, multiplying merchandise, expanding the kiosk size, selling products to other locations, creating strategic new retail business ventures, and seeing supporting factors to overcome the inhibiting factors that occur in the retail business. The supporting factors are the existence of capital, a place that must be strategic, adding or expanding business networks, skills, while the inhibiting factors are the fear of experiencing losses, lack of interest or willingness to sell, the amount of competition, and the way to market goods or products is very bad.